Guide to the LEED Green Associate (GA) Exam - Cottrell, Michelle (Hoboken, NJ : Wiley, 2010)
'Preparing for the LEED-NC Professional Accreditation Exam involves not only an understanding of the LEED-NC rating system, but also of how the LEED process is administered on a project. This study guide for the LEED-NC Professional Accreditation Exam helps architects, building owners, contractors, and others involved in LEED building comprehend each prerequisite and credit in the LEED for New Construction Rating System and understand the responsibilities of the LEED project team administrator in coordinating the project team and in implementing the LEED process. A practice exam completes the student's preparation with hands-on test-taking experience'--
Includes index.
Keywords: Leadership in Energy and Environmental Design Green Building Rating System -- Examinations -- Study guides; Sustainable construction -- Examinations -- Study guides; Sustainable buildings -- Design and construction